Compensation for public holidays coinciding with weekly rest. Critical commentary on SAN no. 88/2026, of May 19, and its projection on the doctrine of the Supreme Court - Toscani Giménez, Daniel (LABOS Revista de Derecho del Trabajo y Protección Social, 2026)
Judgment no. 88/2026 of the Spanish National High Court, delivered on 19 May 2026, constitutes a major development in Spanish labour law regarding public holidays and weekly rest periods. The ruling establishes that public holidays and weekly rest are distinct and independent labour rights, meaning that one cannot absorb or replace the other. Consequently, when a public holiday coincides with a worker’s weekly rest day –particularly Saturdays in ordinary Monday-to-Friday schedules– employees are entitled to effective compensation through an additional day off or an equivalent measure. The judgment expands the doctrine previously established by the Spanish Supreme Court in Judgment 372/2025 of 30 April, which had focused on rotating shift systems and weekly rest overlaps. The National High Court extends that reasoning to ordinary working schedules, thereby recognising the right to compensation even where Saturday is not ordinarily worked. This article analyses the legal foundations of the judgment, its relationship with Article 37 of the Workers’ Statute, and its foreseeable impact on companies, collective bargaining, labour costs and retroactive claims. The study concludes that the ruling may substantially transform the legal treatment of annual public holidays within Spanish labour relations.